Atmospheric feedbacks on Arctic summer sea-ice anomalies in ensemble simulations of a coupled regional climate model - Rinke, Annette; Handorf, Dörthe; Dorn, Wolfgang; Dethloff, Klaus; Moore, John C; Zhang, Xiangdong (Polar Research Institute of China - PRIC, 2018)
Ensemble simulations with the Arctic coupled regional climate model HIRHAM-NAOSIM have been analyzed to investigate atmospheric feedbacks to September sea-ice anomalies in the Arctic in autumn and the following winter. Different “low minus high ice” composites have been calculated using selected model runs and different periods. This approach allows us to investigate the robustness of the simulated regional atmospheric feedbacks to detected sea-ice anomalies. Since the position and strength of the September sea-ice anomaly varies between the different “low minus high ice” composites, the related simulated atmospheric patterns in autumn differ depending on the specific surface heat flux forcing through the ocean-atmosphere interface. However, irrespective of those autumn differences, the regional atmospheric feedback in the following winter is rather insensitive to the applied compositing. Neither the selection of simulations nor the considered period impacts the results. The simulated consistent large-scale atmospheric circulation pattern shows a wave-like pattern with positive pressure anomaly over the region of the Barents/Kara Seas and Scandinavia/western Russia (“Scandinavian-Ural blocking”) and negative pressure anomaly over the East Siberian/Laptev Seas.